Single-valued Neutrosophic Soft Sets in Hyper UP-Algebra (European Journal of Pure and Applied Mathematics, 2023)
In this paper, the notions of SVN hyper UP-algebra and SVNS hyper UP-algebra are introduced, and some of their structural properties are investigated. Moreover, the Cartesian product of SVNS hyper UP-algebra is discussed and proved to be a SVNS hyper UP- algebra. Finally, the homomorphic image and preimage of SVNS hyper UP-algebra under SVNS functions are studied and showed also to be SVNS hyper UP-algebra.
Keywords: hyper algebra